Empathy in mild cognitive impairment: a preliminary clinical comparative study in Southern Switzerland using the interpersonal reactivity index (IRI) and the story-based empathy task (SET) - Arnaud, L.; Morellini, L.; Rege-Colet, L. G.; Pagnamenta, A.; Fontana, E.; Lissi, M.; Morese, R.; Sacco, L. (Frontiers in Aging Neuroscience, 2025)
IntroductionMild Cognitive Impairment (MCI) is a transitional stage between normal aging and dementia, frequently associated with subtle deficits in social cognition. Empathy, a core component of social cognition, encompasses both affective and cognitive dimensions and may be compromised even in prodromal phases of neurodegenerative conditions. Despite its clinical relevance, empathy in MCI remains underexplored, and standardized assessment tools are seldom used in routine diagnostics. Theory of mind is another important aspect of social cognition, and, as with empathy, it is unclear how it is affected at the MCI stage. This study aimed to investigate empathy and theory of mind abilities in individuals with MCI, excluding cases attributable to prodromal frontotemporal dementia, using two validated instruments: the Interpersonal reactivity index (IRI) and the Story-based empathy task (SET).MethodsWe conducted a case–control study involving 23 individuals with MCI and 25 cognitively healthy controls. All participants completed the IRI, while a subsample (19 MCI patients) also underwent the SET. The clinical group included both amnestic and non-amnestic MCI subtypes, with heterogeneous etiologies. Group comparisons were performed on IRI subscales and SET indices to assess both self-reported empathy traits and performance-based socio-cognitive abilities.ResultsThe MCI group exhibited significantly lower scores in the IRI subscales of Empathic Concern and Perspective Taking compared to controls, indicating concurrent affective and cognitive empathy impairments. While no significant differences emerged in individual SET subcomponents, the MCI group showed a significantly lower global SET score, suggesting reduced integrative socio-cognitive performance. These findings should be interpreted with caution given the limited sample size and clinical heterogeneity, which make this a preliminary study.ConclusionThese findings provide preliminary evidence of early empathy-related and theory of mind alterations in MCI, supporting the inclusion of social cognition assessments in standard neuropsychological protocols. The combined use of self-report and task-based instruments may enhance early identification of socio-emotional dysfunctions and inform personalized clinical interventions. The preliminary nature of this study is mainly due to the small sample size and the heterogeneous clinical profiles, which limit generalizability but highlight the need for replication in larger cohorts.